Speaking Strategies of Low-Performing EFL Students at an Islamic Boarding School - M. Ubaidillah Karomi Safari (CV. Kalimasada Group Profesional, 2026)
This study investigated the speaking strategies employed by English as a Foreign Language (EFL) students with low speaking performance and the factors that influenced their choice of strategies. A descriptive qualitative design was used, involving twelve students of MA NWDI Rensing Bat, East Lombok, in the 2025/2026 academic year, who were selected because their speaking test scores fell into the low category. Data were collected through classroom observation, a strategy questionnaire adapted from Oxford's Strategy Inventory for Language Learning, semi-structured interviews, and students' speaking scores, and were analysed using interactive qualitative analysis. The findings revealed that all six strategy categories proposed by Oxford were used at a moderate level of intensity, with cognitive and memory strategies being the most frequently applied and compensation strategies the least. The choice of strategies was influenced mainly by learners' motivation, attitudes, beliefs, gender, age, and speaking proficiency level. The study recommends that teachers explicitly train low-performing learners in cognitive, metacognitive, affective, and social strategies in order to strengthen their speaking ability.